Analysis of environmental regulations at state level in Mexico - Lima-Lima, Julio Adrian; Pech-Canché, Juan Manuel (Acta Universitaria, 2026)
In Mexico, each state must have an environmental protection law; however, the current status of these regulations in the states is unknown. Therefore, the objective was to analyze the status of state environmental laws in Mexico. For each state, environmental laws were identified and analyzed according to different parameters of validity and content using descriptive and inferential statistics (simple linear correlation). Some parameters were found to be significantly correlated (years of antique with total updates), while others had low levels of significance (states and categories). To achieve sustainability, having adequate regulations at the national level is not enough; it is also necessary to pursue the development of state environmental legislation to promote adequate environmental practices at different levels of jurisdiction. There may be a gap in certain topics, such as water, which is poorly legislated at the state level because it falls under federal jurisdiction.